Sol Gabetta at Solsberg Festival - Franck, César 1822-1890; Debussy, Claude 1862-1918 (Karl More Productions, 2012)
At the Solsberg Festival in 2012, the star of cello Sol Gabetta is accompanied by Baïba Skride, Vilde Frang, Ula Uljiona, Bertrand Chamayou and Frank Braley to perform works by Franck and Debussy. The Solsberg Festival was founded in 2006 by Argentinian cellist Sol Gabetta who is now its Artistic Director. In an exceptional site -- the Baroque church St. Martin in Rheinfelden and the Olsberg's cloister --
Keywords: Quintettes pour piano; Piano, Musique de (4 mains); Piano music (4 hands); Piano quintets; Webcast; Internet videos; Vidéos sur Internet